THE EFFECTIVENESS OF ADOBE FLASH VIDEO GAMES TO ENHANCE VOCABULARY COMPREHENSION OF THE SECOND GRADE STUDENTS AT SMPN 2 TAKALAR - Patur Rahman; Kamsinah Sulaiman; Erwin Hafid (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The target of this research was to determine the effect of AdobeFlash Video games to enhance students’ vocabulary comprehension. Therefore, the principle problem was only one, that was to what extent was Adobe Flash Video Games effective to enhance vocabulary comprehension of the second grade students of SMPN 2 Takalar. The study was using quasi Experimental Design, exactly “Non-equivalent Control Group Design. The study involved 60 students, second grade students in SMPN 2 Takalar. This research employed quasi - experimental design with two group pre-test and post-test design. There were two variables in this study; they were independent variable (the use of adobe flash video game) and dependent variable (the vocabulary comprehension of the students). The population of this research was the second grade students at SMPN 2 Takalar which consisted by 336 students. The sample of the research consisted of 60 students which was taken by using purposive sampling technique, 30 students were taken as experimental class and 30 students as control class. The instrument of thisresearch was a written vocabulary used in the pre-test and post-test. The treatment was given by using adobe flash video games. The result of the data of the research indicated that there was a significant difference between the students’ post-test in experimental class and control class. The mean score of the post-test (80.85) in experimental class was greater than the mean score of the post-test (38.61) in control class. The standard deviation of the post-test (43.27) in experimental classwas higher than the standard deviation of the post-test in control class (10.94). From the t-test, the researcher found that the value of the t-test (5.10) was higher than the t-table (2.042) at the level of significance 0.05 with degree of freedom (df) =58. Based on the finding and discussion of the research, the researcher drawn a conclusion that the use of Adobe Flash Video Games was effective to enhance the vocabulary comprehension of the second grade students at SMPN 2 Takalar.